Lateral skull base Inflammatory pseudotumor: A systematic review. (17th April 2015) - Spinazzi, Eleonora F.; Desai, Stuti V.; Fang, Christina H.; Jyung, Robert W.; Liu, James K.; Baredes, Soly; Eloy, Jean Anderson
<x xml:space="preserve">Abstract</x> Objective Inflammatory pseudotumor (IPT) of the lateral skull base is a rare nonneoplastic inflammatory process of unknown cause often mistaken for malignancy or infection. This systematic review aims to analyze all reported cases of lateral skull base IPT to date in order to provide insight into the management of this uncommon lesion. Data Sources MEDLINE/PubMed database. Review Methods The MEDLINE/PubMed databases were searched for articles related to lateral skull base IPT. A bibliography review of the search results was then performed for additional articles. Demographics, presentation, radiographic findings, treatment, follow‐up, and outcome were analyzed. Results Thirty articles describing 39 patients were reviewed. The most common presenting symptom was hearing loss (53.8%). The mastoid bone had the highest incidence of IPT (61.5%). Computed tomography (CT) was the most utilized imaging modality. The lesion appeared isointense on T1‐weighted magnetic resonance imaging (MRI) (75.0%) and hypointense on T2‐weighted MRI (62.5%). Histopathological analysis showed fibrosis (96.9%) with inflammatory cell infiltration (100.0%). Surgical resection (alone or in combination with other treatments) was the most common treatment modality (92.3%), producing the greatest number of disease‐free patients overall (96.0%). The mean follow‐up time was 21.6 months, at which point 34.4% of patients showed improvement and 31.3% were completely disease‐free. Conclusion This review is the most comprehensive analysis of lateral skull base IPT to date. A thorough workup including clinical exam, imaging, and biopsy is essential for diagnosis. Surgical excision is the most common and most successful treatment modality, followed by surgery with corticosteroids. Laryngoscope, 125:2593–2600, 2015